A genome-wide association study on meat consumption in a Japanese population: the Japan Multi-Institutional Collaborative Cohort study. (11th October 2021) - Nakamura, Yasuyuki; Narita, Akira; Sutoh, Yoichi; Imaeda, Nahomi; Goto, Chiho; Matsui, Kenji; Takashima, Naoyuki; Kadota, Aya; Miura, Katsuyuki; Nakatochi, Masahiro; Tamura, Takashi; Hishida, Asahi; et al.
Abstract: Recent genome-wide association studies (GWAS) on the dietary habits of the Japanese population have shown that an effect rs671 allele was inversely associated with fish consumption, whereas it was directly associated with coffee consumption. Although meat is a major source of protein and fat in the diet, whether genetic factors that influence meat-eating habits in healthy populations are unknown. This study aimed to conduct a GWAS to find genetic variations that affect meat consumption in a Japanese population. We analysed GWAS data using 14 076 participants from the Japan Multi-Institutional Collaborative Cohort (J-MICC) study. We used a semi-quantitative food frequency questionnaire to estimate food intake that was validated previously. Association of the imputed variants with total meat consumption per 1000 kcal energy was performed by linear regression analysis with adjustments for age, sex, and principal component analysis components 1–10. We found that no genetic variant, including rs671, was associated with meat consumption. The previously reported single nucleotide polymorphisms that were associated with meat consumption in samples of European ancestry could not be replicated in our J-MICC data. In conclusion, significant genetic factors that affect meat consumption were not observed in a Japanese population.